Pengaruh Metode Pengeringan Terhadap Kadar Total Fenolik Ekstrak Daun Singkil (Premna corymbose Rottl et Wild) - Margareta Retno Priamsari; Putri Marsela Danti (Indonesian Journal on Medical Science, 2022)
Singkil leaves (Premna corymbose Rottl et Wild) contain secondary metabolites in the form of flavonoids, saponins, triterpenoid/steroid tannins and phenolic compounds. Phenolic compounds have antioxidant, antitumor, antiviral and antibiotic activity. The drying process of simplicia will have an impact on the content of phenolic compounds. This study aims to determine the effect of the drying method on the total phenolic compounds in singkil leaf extract. This type of research is experimental. Singkil leaf simplicia drying method was carried out using an oven at a temperature of 50°C and air-dried. The extraction method uses maceration with 70% ethanol as solvent. Determination of total phenolic content was carried out by colorimetric method using UV-Vis spectrophotometry with Follin Chiocalteau reagent and gallic acid as standard. The calibration curve was made in 5 concentration series, namely 6,8,10,12, and 14 ppm. The absorbance was calculated at a wavelength of 662.85nm and the readings were used as a determinant of the total phenolic content of the singkil leaf extract. The results showed that the drying method could significantly affect the total phenolic content of singkil leaf extract. The total phenolic content of singkil leaf extract using the wind dry method was 13.37±0.00% while the 50oC oven drying method was 10.64±0.00057%.